UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MELALUI SIMULATION LEARNING DENGAN MODEL HOLLYWOOD SQUARES REVIEW - Rohmawati, Rohmawati; Al ‘Ayubi, Sholahuddin; Susilaningtyas, Tri (FKIP Universitas Islam Jember, 2019)
Research on Efforts to Increase Activities and Learning Outcomes of the Subject of Data Presentation through Simulation Learning with the Hollywood Squares Review Model. Based on the results of the study, it was found that the application of the Simulation Learning learning method with the Hollywood Square Review learning model could increase student activity and learning outcomes in the data presentation material at MTs Miftahul Ulum This can be seen from an increase in student activity in each cycle and an increase in the average percentage of student learning outcomes from cycle I to cycle II. In the final test of the cycle I, the average percentage of student learning outcomes was 15.38% and the average percentage of tests in the second cycle was 76.92%. Keywords: Simulation Learning, Hollywood Squares Review, Student Activities, Learning outcomes